Abu Dzarr Al-Ghifari dan Perlawanan Ekonominya - Santosa Irfaan (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2009)
Abu Dzarr al-Ghifari has a unique character, especially in conveying has an opinion. He is one of the closest men to Muhammad Prophet, and his ideas are not only about tasawuf but also about other points, i.e economy.